Will remote electronic voting systems increase participation?. (19th September 2005) - Houston, Andrea L.; Yao, Yurong; Okoli, Chitu; Watson, Edward
Remote electronic voting systems (REVSs) have become a viable mechanism for official political elections. It can enable remote voting, facilitate monitoring, voting and tallying, and report immediate results. However, it is uncertain whether the use of REVS could increase citizens' participation in elections. This study examines this question in the USA. By analysing the data from multiple sources, we found that web-based REVS use can significantly increase the participation of non-voting citizens, and that young adults have a strong preference to using REVS. The implications and the recommendations about the use of REVS are also discussed.